DEVELOPMENT OF MATHEMATICS MODULE BASED ON GUIDED DISCOVERY ON RECTANGULAR MATERIALS FOR STUDENTS OF CLASS VII SMP - Hafidina Nur Fi Rahman; Suparman Suparman (Universitas Ahmad Dahlan, 2018)
The limitations of materials resulting in learner's optimal learning can not cause learning activities centered on the teacher; this resulted in a low level of self-reliance and active students in learning. This research aims to develop modules, testing the feasibility of modules, and knowing the student response to the development of a module of mathematics based discovery learning on the material in rectangular to Junior High School students of class VII. Procedure for adapting the development of models of research and development ( R&D) include the stage of identifying the potential and problems, collect data, crafting products, product validation, revision products, product trials, revision product, trial use, revision of the product, the final product. This is a subject matter expert, media, and student. This research object is a module of mathematical-based discovery learning on the rectangular material of Junior High School (SMP) students of Class VII. Data collection techniques in the form of sheets of interview and question form. With test instruments through the validation and analysis of data using lecturer analysis question form and analysis of a mathematical module's feasibility. Based on the study results, the module's feasibility by the material obtained an average score of 102 with the category very good. The eligibility module by media expert earns an average score of 120,67 with category very good. Now the response of students obtained a scoring average of 131,80 with category very good. So, mathematical modules on a rectangle of material worth